DISTRIBUTION PATTERNS AND POTENTIAL OF SONOKELING (Dalbergia latifolia) IN THE PROTECTED FOREST BLOCK OF KPH SEJORONG MATAIYANG WEST NUSA TENGGARA (Jurnal Rimba Lestari, 2023)
Protected forests play a critical role in biodiversity conservation and ecosystem stability but are often threatened by exploitation. Dalbergia latifolia (sonokeling) is a high-value species experiencing population decline due to overexploitation. This study aims to analyze the potential and distribution of sonokeling in the Sejorong Mataiyang Protected Forest Block, West Sumbawa Regency. Data were collected using the n-tree distance sampling method and vegetation analysis with the Importance Value Index (IVI) to measure density, frequency, and dominance. The results show that Dalbergia latifolia dominates across all vegetation levels (seedlings, saplings, poles, trees). At the seedling and sapling levels, plot 12 recorded the highest relative density (KR) and relative frequency (FR) values, both at 27.727%. At the pole level, the highest dominance (11.048%) was found in plot 5, while at the tree level, the highest dominance value (9.128%) was recorded in plot 9. These findings highlight sonokeling’s strong regeneration and adaptability to various environmental conditions. Sonokeling holds significant potential for conservation through ecosystem-based management and protection from overexploitation. This study provides a scientific basis for conservation efforts, supporting the sustainability of local ecosystems.
Keywords: Distribution Pattern; Potential; Sonokeling